CD4+ T cell memory is impaired by species-specific cytotoxic differentiation, but not by TCF-1 loss - Hofland, Tom; Danelli, Luca; Cornish, Georgina; Donnarumma, Tiziano; Hunt, Deborah M.; de Carvalho, Luiz P. S.; Kassiotis, George (Frontiers in Immunology, 2023)
CD4+ T cells are typically considered as ‘helper’ or ‘regulatory’ populations that support and orchestrate the responses of other lymphocytes. However, they can also develop potent granzyme (Gzm)-mediated cytotoxic activity and CD4+ cytotoxic T cells (CTLs) have been amply documented both in humans and in mice, particularly in the context of human chronic infection and cancer. Despite the established description of CD4+ CTLs, as well as of the critical cytotoxic activity they exert against MHC class II-expressing targets, their developmental and memory maintenance requirements remain elusive. This is at least in part owing to the lack of a murine experimental system where CD4+ CTLs are stably induced. Here, we show that viral and bacterial vectors encoding the same epitope induce distinct CD4+ CTL responses in challenged mice, all of which are nevertheless transient in nature and lack recall properties. Consistent with prior reports, CD4+ CTL differentiation is accompanied by loss of TCF-1 expression, a transcription factor considered essential for memory T cell survival. Using genetic ablation of Tcf7, which encodes TCF-1, at the time of CD4+ T cell activation, we further show that, contrary to observations in CD8+ T cells, continued expression of TCF-1 is not required for CD4+ T cell memory survival. Whilst Tcf7-deficient CD4+ T cells persisted normally following retroviral infection, the CD4+ CTL subset still declined, precluding conclusive determination of the requirement for TCF-1 for murine CD4+ CTL survival. Using xenotransplantation of human CD4+ T cells into murine recipients, we demonstrate that human CD4+ CTLs develop and persist in the same experimental conditions where murine CD4+ CTLs fail to persist. These observations uncover a species-specific defect in murine CD4+ CTL persistence with implications for their use as a model system.